By Using Satellite Navigation Systems Observation Of Landslides And Migration Events - Safarov T. U.; Suyunov S. A.; Samankulov S. R.; Obloqulova S. S. (Academia One Publishing, 2024)
This paper discusses the study of modern conditions and the problem of landslide phenomena in rocks by their types. The conditions and reasons for the formation of landslide areas are considered. It is shown that, subject to a number of necessary conditions, a landslide is, first of all, a function of the steepness and height of the slope, and only then a function of the presence of groundwater. The issues of using modern satellite navigation systems in monitoring landslide phenomena are considered. Methods for observing landslide phenomena using modern satellite systems are presented. Based on the results of satellite navigation observations of signs installed on the surface of the landslide, the magnitude, direction and speed of horizontal and vertical displacements were calculated. The accuracy of the specified characteristics has been assessed
Keywords: water erosion; landslides; seismic shocks; soil erosion